Associations among body dissatisfaction, gender, and three latent profiles of religiosity. Issue 4 (21st April 2018) - Audette, Lillian M.; Barry, Carolyn M.; Carlucci, Marianna E.; Hardy, Sam
ABSTRACT: Body dissatisfaction is a too-common issue for young women in the US. Body dissatisfaction is a rising issue with young men too, although their average body dissatisfaction remains lower than young women's. Religiosity has been negatively linked to body dissatisfaction for women, but the relation for men is unclear. The current study ( N = 5104) built upon a previous latent profile analysis of a large, diverse sample of US. college students Multi-Site University Study of Identity and Culture (MUSIC). We examined whether body dissatisfaction scores were related to three religious classes, when depressive symptoms were controlled for, and whether gender moderated that potential relation. Body dissatisfaction scores were significantly related to religious class. Gender had a main effect although not a moderating effect: men had better body dissatisfaction than women did, and their religious class similarly affected their body dissatisfaction scores. Religiosity appears important for emerging adult men's body dissatisfaction, like for emerging adult women.